2017
DOI: 10.14744/anatoljcardiol.2016.7411
|View full text |Cite
|
Sign up to set email alerts
|

Role of simvastatin and RORα activity in the macrophage apoptotic pathway

Abstract: Objective: Atherosclerosis is a chronic inflammatory condition and is one of the main causes of death worldwide. Macrophages play important roles in the formation of atherosclerotic plaques. Apoptosis is progressively observed while plaques develop, although the precise mechanisms and outcomes of apoptosis in atherosclerosis development and progression are still contradictory. This study was conducted to explore the effects of simvastatin and retinoic acid receptor-related orphan receptor alpha (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…This increased inflammation after SIM therapy that was observed starting from day 3 in the BPVC-injured muscles provided evidence that SIM did not exert an anti-inflammatory effect in the postinjury skeletal muscle regeneration. This conclusion is not in agreement with previous studies that revealed the ability of statins to decrease the recruitment of neutrophils and macrophages under many conditions [ 8 10 , 29 ]. Furthermore, as observed in the SIM-treated group, a persistently high level of inflammation should accelerate the removal of cellular debris, reduce the necrosis duration, and positively affect regeneration, but these effects were not observed in the present study.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This increased inflammation after SIM therapy that was observed starting from day 3 in the BPVC-injured muscles provided evidence that SIM did not exert an anti-inflammatory effect in the postinjury skeletal muscle regeneration. This conclusion is not in agreement with previous studies that revealed the ability of statins to decrease the recruitment of neutrophils and macrophages under many conditions [ 8 10 , 29 ]. Furthermore, as observed in the SIM-treated group, a persistently high level of inflammation should accelerate the removal of cellular debris, reduce the necrosis duration, and positively affect regeneration, but these effects were not observed in the present study.…”
Section: Discussioncontrasting
confidence: 97%
“…This conclusion is supported by previous studies indicating that statins inhibit the secretory activity of neutrophils and macrophages and regulate the expression of factors and molecules that control their phagocytic action [ 10 , 30 , 31 ]. Moreover, the improper phagocytic activity of inflammatory cells detected after SIM treatment could also be the result of increased apoptosis of neutrophils and macrophages, as suggested by other investigators [ 9 , 29 ] and will be the subject of further research. Furthermore, taking into account the results of the present study and the fact that M1 and M2 macrophage activity occurs starting on day 3 of the postinjury skeletal muscle regeneration, it should be assumed that SIM affects these inflammatory cells rather than neutrophils.…”
Section: Discussionmentioning
confidence: 76%
“…Atherosclerosis is the major risk factor for cardiovascular disease, and the number of deaths from this disease is increasing every year; therefore, the prevention of atherosclerosis and cardiovascular disease is quite an important problem (Çoban et al . ). Lifestyle‐related diseases such as obesity, hypertension, diabetes mellitus and disorders of lipid metabolism potentially cause atherosclerosis.…”
Section: Introductionmentioning
confidence: 97%
“…Studies with triacsin C have shown that inhibiting ACS leads to apoptosis in human T lymphoblastoma [ 26 ], glioma [ 27 , 28 ], and hepatocellular carcinoma cells [ 29 ] through pathways mediated by mitochondria. Another study showed that treatment with simvastatin, a lipid-lowering drug, decreases proliferation of human acute monocytic leukaemia (THP-1) macrophage cells [ 30 ]. Based on these findings, it has been hypothesised that the inhibition of ACS by triacsin C would impair DHA metabolism, which contributes to cytotoxicity-induced apoptosis by DHA in RL95-2 endometrial carcinoma.…”
Section: Introductionmentioning
confidence: 99%